FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN MAHASISWA AKUNTANSI: STUDI PERAN FASILITAS KAMPUS, KUALITAS PENGAJARAN DOSEN, RELASI MAHASISWA, BEBAN TUGAS DAN AKTIVITAS ORGANISASI - Syaiful, Claudya Sizika Beatrix; Hwihanus (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze the factors that influence accounting student satisfaction at the University of 17 August 1945 Surabaya, including aspects of campus facilities, teaching quality, student relations, workload, and organizational activities. Data were collected through a questionnaire with a Likert scale to 5 students as a sample. The results of the Pearson correlation analysis showed that most of the relationships between variables were not statistically significant (p value > 0.05), although there was a weak to moderate correlation. The strongest relationship was found between the total variable and workload (r = 0.748), but was not significant (p = 0.146). In conclusion, this study indicates the need for additional data collection and further analysis to understand the relationship between variables that influence student satisfaction in more depth.